Some Improvements on Hermite-Hadamard's Inequalities for $s$-Convex Functions (Journal of Mathematical Study, 2018)
Using an integral identity for a once differentiable mapping, this paper establishesHadamard's integral inequalities for $s$-convex and $s$-concave mappings. Inparticular, our results improve and extend some known ones in the literature. Finally,these inequalities are applied to special means.